2020
DOI: 10.1007/s11524-020-00504-z
|View full text |Cite
|
Sign up to set email alerts
|

Prison Population Reductions and COVID-19: A Latent Profile Analysis Synthesizing Recent Evidence From the Texas State Prison System

Abstract: People in prison are particularly vulnerable to infectious disease due to close living conditions and the lack of protective equipment. As a result, public health professionals and prison administrators seek information to guide best practices and policy recommendations during the COVID-19 pandemic. Using latent profile analysis, we sought to characterize Texas prisons on levels of COVID-19 cases and deaths among incarcerated residents, and COVID-19 cases among prison staff. This observational study was a seco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 11 publications
1
37
0
1
Order By: Relevance
“…Furthermore, analysis of hospitalizations (Figure 3) reveals that older and medically vulnerable residents should receive additional protections beyond vaccine priority, such as lower occupancy housing and additional NPIs. Our study demonstrates the benefits of lower occupancy housing and points to the potential impact of depopulation (16), which other analyses have concluded is an important strategy to reduce transmission (34,35).…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, analysis of hospitalizations (Figure 3) reveals that older and medically vulnerable residents should receive additional protections beyond vaccine priority, such as lower occupancy housing and additional NPIs. Our study demonstrates the benefits of lower occupancy housing and points to the potential impact of depopulation (16), which other analyses have concluded is an important strategy to reduce transmission (34,35).…”
Section: Discussionsupporting
confidence: 60%
“…Our study shows the benefits of lower occupancy housing and points to the potential impact of depopulation, 18 which other studies have also highlighted. [30][31][32] Future work could include an assessment of other prevention measures, such as holding activities outdoors or limiting contact across yards or buildings within a prison.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of Texas prisons described three profiles of COVID-19 outbreaks-low outbreak, high outbreak, and high death-and found that maintaining housing at 85% capacity reduced risk of COVID-19 infection and death. 4 A case study of the British Columbia prison system described successful prevention of COVID-19 outbreaks before the rollout of vaccines using a combination of education, screening, testing, isolation, quarantine, physical distancing, and sanitisation. 5 In The Lancet Public Health, Theresa Ryckman and colleagues 6 have added to this body of research by modelling COVID-19 public health policies in the California state prison system.…”
Section: Reducing Covid-19 Outbreaks In Prisons Through Public Health-centred Policiesmentioning
confidence: 99%